A combined Clostridium perfringens/Trueperella pyogenes inactivated vaccine induces complete immunoprotection in a mouse model. (May 2017) - Zhang, Wenlong; Wang, Pu; Wang, Bing; Ma, Bo; Wang, Junwei
Abstract: Clostridium perfringens ( C. perfringens ) and Trueperella pyogenes ( T. pyogenes ) are two bacterial pathogens frequently associated with wound infections and following lethal complications in livestock. However, prudent use of antimicrobial agents is highly required given the emergence of multidrug-resistant strains of both bacteria and need for food safety. In the current study, a combined vaccine, composed of inactivated C. perfringens and T. pyogenes, was prepared. The amount of formaldehyde being used to inactivate two bacteria was optimized to retain the immunogenicity of antigens. Three adjuvants were tested for their potency in improving specific immune responses against the candidate antigens. Then inactivated combined C. perfringens / T. pyogenes vaccine was prepared using inactive cultures of two organisms. The ratio of inactive cultures of two organisms for preparation of combined vaccine was optimized to gain effective protective immunity against the two pathogens. Results revealed that combined C. perfringens / T. pyogenes inactive vaccine can elicit high level of exotoxins and cell-associated antigen-specific antibodies and induce complete protection against C. perfringens and T. pyogenes infections in mice. The combined vaccine could be used as an alternative of antibiotics for prevention of C. perfringens and T. pyogenes infections in animals.